Cavernous haemangioma of male breast - Chidambaram, Asha; Shetty, Mahendra Kumar; Atula, Ashok (International Journal of Research in Medical Sciences, 2017)
We report a rare case of a cavernous hemangioma arising in a male breast. A 53 year old man first noticed 1×1 cm nodule just below his left nipple since 2 years. It was enlarging over a period to the present size. He came to our hospital, it was size of (2×1 cm), was a firm and cystic with a rather smooth surface, and mobile with in breast just medial to left nipple. Fine needle aspiration cytology (FNA) failed to obtain proper material except for old bloody fluid or necrotic connective tissue, precluding a correct diagnosis preoperatively suggesting cystic lesion with bloody aspirate. Lumpectomy or excision biopsy was subsequently performed. Histological, it was found to be a cavernous hemangioma. In such a case, complete excision is recommended to exclude the possibility of an underlying malignant lesion.